Ultrasonography indicators for predicting difficult intubation: a systematic review and meta-analysis - Sotoodehnia, Mehran (BMC Emerg Med, 2021)
BACKGROUND: Ultrasonography (US) is recently used frequently as a tool for airway assessment prior to intubation (endotracheal tube (ETT) placement), and several indicators have been proposed in studies with different reported performances in this regard. This systematic review and meta-analysis reviewed the performance of US in difficult airway assessment. METHODS: This systematic review and meta-analysis was conducted according to the guideline of Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) and the Cochrane book. All the studies that had carried out difficult airway assessments using US, had compared the indicators in difficult and easy groups, and had published the results in English by the time we conducted our search in April 28, 2020, were included. RESULTS: In the initial search, 17,156 articles were retrieved. After deleting the duplicate articles retrieved from multiple databases, 7578 articles remained for screening based on the abstracts and titles. Finally, the full text of 371 articles were assessed and the data from 26 articles were extracted, which had examined a total of 45 US indicators for predicting difficult intubation. The most common US index was the “thickness of anterior neck soft tissue at the vocal cords level”. Also, “skin to epiglottis” and “anterior neck soft tissue at the hyoid bone level” were among the most common indicators examined in this area. CONCLUSION: This systematic review showed that US can be used for predicting difficult airway. Of note, “skin thickness at the epiglottis and hyoid levels”, “the hyomental distance”, and “the hyomental distance ratio” were correlated with difficult laryngoscopy in the meta-analysis. Many other indicators, including some ratios, have also been proposed for accurately predicting difficult intubation, although there have been no external validation studies on them.